Seasonal variations in abundance and diversity of copepods in Mond River estuary, Bushehr, Persian Gulf - ALIAKBAR HEDAYATI; MOJTABA POULADI; AMIR VAZIRIZADEH; AMIR QADERMARZI; NEDA MEHDIPOUR (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Hedayati A, Pouladi M, Vazirizadeh A, QadermarziA, Mehdipour N. 2017. Seasonal variations in abundance and diversity of copepods in Mond River estuary, Bushehr, Persian Gulf. Biodiversitas 18: 447-452. The present study was carried out to investigate the abundance and biodiversity of copepods from Mond River (MR) estuary, Bushehr, Persian Gulf during 4 seasons and their relationships with environmental factors. The water samples were collected in mid-season from spring 2012 to winter 2013 for one year period. Copepod samples were collected by using of 140 µm plankton net with 25 cm mouth diameter and vertical towing in all stations. Copepod assemblages were comprised of 4 orders, 13 families and 10 genera. Orders were included; Calanoida, Cyclopoida, Poecilostomatoida, Harpacticoida and Genera were included: Cathocalanus, Acrocalanus, Paracalanus, Subeucalanus, Centropages, Temora, Calanopia, Labidocera, Pontella, Acartia, Oithona, Oncaea, Corycaeus, Microsetella, Microsetella and Euterpina. The order Calanoida with 10 genera was the most diverse and dominant order between Identified orders. The means (±SE) of copepods abundance were recorded in spring (5853.4±1826.19 Individual m-3), in summer (6707.6±1930.15 Ind. m-3), in fall (4393.6±1263.37 Ind. m-3) and in winter (3400±763.98 Ind. m-3), respectively. Simpson and Shannon-Wiener biodiversity indices were obtained in spring (0.87±0.11 and 2.86±0.19), in summer (0.89±0.006 and 3.11±0.15), in fall (0.86±0.13 and 2.66±0.2) and in winter (0.83±0.12 and 2.39±0.15), respectively. The copepod assemblages had most amounts of diversity and abundance at station 5 in all seasons. Pearson correlation showed significant correlation between copepod diversity and abundance with salinity, pH and temperature. Results showed that salinity factor was more effective environmental factor on Simpson (0.01> P and r=0.783) and Shannon-Weiner indices (0.01> P and r=0.727), and copepods abundance (0.01> P and r=0.664) in MR estuary. Keywords: Abundance, copepod, diversity, environmental factor, Mond Estuary